Efecto de la suplementación alimenticia con balanceados artesanales en el rendimiento productivo de caprinos (Capra hircus) en engorde, en Totumos - Zapotillo - Castillo Requena, Blanca Liliana (2024)
In the Totumos neighborhood of the Zapotillo canton of Loja province, goat production is an activity of great economic importance, however, it is still of low profitability mainly due to nutritional deficiencies. Therefore, the objective of this research was to evaluate the effect of feed supplementation with handmade feed on the productive performance of fattening goats. The research was of the experimental type, with three treatments and three replications. Twenty-seven experimental units with an average age of 12 weeks were used, of the Creole x Anglo Nubian crossbreed, in which the following variables were analyzed: feed consumption, weight gain, feed conversion, mortality, carcass yield and profitability. The analysis of variance and comparison of means using Tukey's test with 5% significance was used. The results show that treatment 3 (hand-balanced with the inclusion of faique) obtained the best results, with a feed consumption of 8.25 kg, a weight increase of 1.50 kg, a feed conversion of 2.18 kg, and a profitability of 47.81 kg. It is concluded that the inclusion of faique (Acacia macracantha) versus the inclusion of charán (Caesalpinia paipa) in the balanced rations has a positive effect on the productive performance and profitability in goat fattening.